FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM PELAKSANAAN PEMBANGUNAN DESA DIDESA BATAKA KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT - RADING, NOFITRI; LENGKONG, FLORENCE DAICY; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2018)
Development aims to create a just and prosperous society, to improve the community's harmony in the villageroles of village government and BPD is very important to realize the welfare of the community, to succeed constructionthat has been agreed together in muslembang should be implemented as planned. This study uses qualitative researchmethods tailored to the title and the problem of the purpose of this study is To determine the BPD supervision functionin the implementation of village development in performing the BPD Supervision function on the performance of thevillage government, to supervise how the implementation of development in the field of development in Bataka Village,West Halmahera.BPD supervision function in the implementation of rural development has not been good, and theresult of poor development, resulting from the function of BPD that does not perform the task well and the lack ofcooperation between the BPD with the village government and BPD supervision function in the village is very helpfulfor the success of development, the presence of direct and indirect supervision then the desired development can beachieved.Keywords: Supervision, Implementation of Development, Village Consultative Agency